IL-10 modified mRNA monotherapy prolongs survival after composite facial allografting through the induction of mixed chimerism - Ana Elena Aviña; Dante De Paz; Shu-Chun Huang; Kuan-Hung Chen; Yun-Ching Chang; Chin-Ming Lee; Chia-Hsien Lin; Fu-Chan Wei; Aline Yen Ling Wang (Elsevier, 2023)
Vascularized composite allotransplantation has great potential in face transplantation by supporting functional restoration following tissue grafting. However, the need for lifelong administration of immunosuppressive drugs still limits its wide use. Modified mRNA (modRNA) technology provides an efficient and safe method to directly produce protein in vivo. Nevertheless, the use of IL-10 modRNA-based protein replacement, which exhibits anti-inflammatory properties, has not been shown to prolong composite facial allograft survival. In this study, IL-10 modRNA was demonstrated to produce functional IL-10 protein in vitro, which inhibited pro-inflammatory cytokines and in vivo formation of an anti-inflammatory environments. We found that without any immunosuppression, C57BL/6J mice with fully major histocompatibility complex (MHC)-mismatched facial allografts and local injection of IL-10 modRNA had a significantly prolonged survival rate. Decreased lymphocyte infiltration and pro-inflammatory T helper 1 subsets and increased anti-inflammatory regulatory T cells (Tregs) were seen in IL-10 modRNA-treated mice. Moreover, IL-10 modRNA induced multilineage chimerism, especially the development of donor Treg chimerism, which protected allografts from destruction because of recipient alloimmunity. These results support the use of monotherapy based on immunomodulatory IL-10 cytokines encoded by modRNA, which inhibit acute rejection and prolong allograft survival through the induction of donor Treg chimerism.